Improving The Tenth Grade Students’ Ability of Writing Descriptive Text Using Town Map at Sma Negeri 2 Trenggalek - Risma Ayu Firdayanti; Wawan Prasetyo (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2022)
The objective of the research is to know how Town Map can improve the tenth-grade students’ ability of writing descriptive text at SMA Negeri 2 Trenggalek in the academic year 2012/2013. The research design used was collaborative action research. This research was conducted in two cycles and each cycle was divided into four stages, they are planning, acting, observing, and reflecting. The subjects of this study were students of class X-G in the academic year 2012/2013 which consisted of 35 students. The research instruments used were tests, questionnaires, observation sheets, and field notes. Data collected with observation sheets were analyzed qualitatively, while data collected by tests and questionnaires were analyzed quantitatively. The result of this research showed that the use of Town Map can improve the writing ability of X-G class students of SMA Negeri 2 Trenggalek in writing descriptive text. This can be seen from the increase of the percentage in the pre-test, post-test in cycle one, and post-test in cycle two. The results of the pre-test showed that only 10 students (29%) out of 35 students successfully passed the writing test. Then, in the first post-test cycle there were 17 (49%) of 35 students passed and 30 students (86%) of 35 students succeeded and had achieved the success criteria in the second cycle.